Perawatan dan Perbaikan Pompa Sentrifugal 800LC-38A Untuk Sirkulasi Air Pendingin Pada PLTU - Alifur Rahman; Zikri Hamdani; Darman Dapersal Dinar; Menhendry; Yuli Yetri (Pusat Pengembangan, Penelitian dan Pengabdian kepada Masyarat (P4M) Politeknik Manufaktur Bandung (Polman Bandung), 2021)
800LC-38A Centrifugal Pump is a very important pump in the 2x15 MW PLTU, PT. Industrial Area Dumai-Wilmar Group, Riau Province. Where the efficiency of the 2x15 MW power plant is quite influenced by this pump. The 800LC-38A Centrifugal Pump functions as a cooling water circulation at the 2x15 MW PLTU so that productivity at the 2x15 MW PLTU runs smoothly. The aim is to explain the damage that occurs and be able to perform maintenance and repairs to the pump. Maintenance measures at the 800LC-38A Centrifugal pump are Preventive Maintenance, Predictive Maintenance and Corrective Maintenance. The problem that occurs in this pump is the reduced pump capacity and high vibration. While damage occurred to pump components such as pump shafts, shaft sleeves and casings which were corroded, teflon / guide bearings were damaged, and pump impellers were cracked due to cavitation on the pump. Maintenance carried out on the 800LC-38A Centrifugal pump in the form of checking the condition of the bearing, checking vibration and lubrication. The repairs made to the pump shaft that is corroding is by metalizing, for the case of the pump that is corroded can be overcome by coating / coating, shaft sleeve that is corroding and the impeller which is cracked due to cavitation cannot be repaired but a component replacement must be done.